2020
DOI: 10.2337/db19-0807
|View full text |Cite
|
Sign up to set email alerts
|

MG53 Does Not Manifest the Development of Diabetes in db/db Mice

Abstract: MG53 is a member of the TRIM protein family that is predominantly expressed in striated muscles and participates in cell membrane repair. Controversy exists regarding MG53's role in insulin signaling and manifestation of diabetes. We generated db/db mice with either whole-body ablation or sustained elevation of MG53 in the bloodstream in order to evaluate the physiological function of MG53 in diabetes. To quantify the amount of MG53 protein in circulation, we developed a monoclonal antibody against MG53 with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 43 publications
(97 reference statements)
10
57
1
Order By: Relevance
“…While we cannot exclude the possibility that different reagents may lead to different results, our data raise significant doubts about the involvement of MG53 in the regulation of insulin signaling. In addition, our data are consistent with recent reports from the Ma's lab who used alternative strategies to come to the same conclusions [16,19]. First, they showed using transgenic mice that sustained elevation of plasma MG53 levels does not compromise insulin signaling in skeletal muscle as well as glucose handling when mice were placed under high fat diet.…”
Section: Transfection Of Rnai Targeting Mg53 Led To a Robust And Reprsupporting
confidence: 92%
See 1 more Smart Citation
“…While we cannot exclude the possibility that different reagents may lead to different results, our data raise significant doubts about the involvement of MG53 in the regulation of insulin signaling. In addition, our data are consistent with recent reports from the Ma's lab who used alternative strategies to come to the same conclusions [16,19]. First, they showed using transgenic mice that sustained elevation of plasma MG53 levels does not compromise insulin signaling in skeletal muscle as well as glucose handling when mice were placed under high fat diet.…”
Section: Transfection Of Rnai Targeting Mg53 Led To a Robust And Reprsupporting
confidence: 92%
“…We tried to measure MG53 levels in plasma samples from these animals. However, western blot analyses led to the detection of MG53 at a lower size (data not shown) with doubts about the accuracy of the band for the MG53 signal in line with observations made by other groups [16][17][18].…”
Section: Resultssupporting
confidence: 71%
“…This would also imply that the high levels of circulating MG53 present in tPA-MG53 mice could block the insulin pathway and greatly facilitate the development of diabetes. However, as mentioned above, tPA-MG53 mice live a healthy lifespan and when crossed with db/db mice, tPA-MG53/db/db mice are indistinguishable from db/db littermates in terms of growth rate, glucose tolerance test, and insulin tolerance test (Bian et al, 2019;Wang et al, 2020). These studies highlight the deep controversies surrounding the protein that will need to be resolved by future studies.…”
Section: Controversial Role Of Mg53 In Diabetesmentioning
confidence: 78%
“…tPA-MG53 mice live a healthy lifespan with enhanced tissue repair and regeneration capacity (Yao et al, 2016;Bian et al, 2019). To test the role of elevated circulating MG53 in the development of diabetes, we crossed tPA-MG53 mice with db/db mice and found that tPA-MG53/db/db mice develop diabetes at a rate similar to its db/db littermates, suggesting overexpression of MG53 has negligible effects on the development of diabetes (Wang et al, 2020). A separate transgenic mouse model with overexpression of MG53 was generated by Ham and Mahoney (2013).…”
Section: Controversial Role Of Mg53 In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation